Local Religious Inclusivism and the Role of State-Driven Literacy in Resisting Transnational Ideologies: a Study of Kingking Tuban - Aries Hamidah; Moh. Fiqih Firdaus; Wardatul Karomah (INSTITUT AGAMA ISLAM TARBIYATUT THOLABAH LAMONGAN, INDONESIA, 2026)
This study highlights the significance of inclusive religious literacy and practice in addressing the penetration of transnational ideologies in Indonesia. Focusing on the community of Kingking, Tuban, it examines how Muslim–Christian harmony has been sustained through the strength of local culture and community-based moral authority. Conceptually, the research integrates Homi K. Bhabha’s theory of cultural hybridity, Michel Foucault’s notion of power relations, and Axel Honneth’s concept of mutual recognition to explain the social dynamics underlying religious inclusivity. Employing a qualitative-descriptive approach, data were collected through field observations, in-depth interviews, and the analysis of historical documents. The findings reveal that local religious identity is shaped by cultural hybridity and reciprocal recognition between communities. Critical religious literacy and the active roles of kyai and pastors contribute to social resilience against exclusive ideologies. The study concludes that Tuban’s model of local inclusivism may serve as a national paradigm for strengthening religious moderation and postcolonial pluralism.